Efforts to Drill the Critical Thinking Skills on Momentum and Impulse Phenomena Using Discovery Learning Model - Baiq Hanum Ekayanti; Saiful Prayogi; Syifa’ul Gummah (International Journal of Essential Competencies in Education, 2022)
Critical thinking is needed as a guarantee of student success in solving a problem, and critical thinking training starts from students' learning experiences when they are in school. It is believed that one's skills in critical thinking influence student success in a broader spectrum of learning outcomes. It's just that the facts on the ground show that students are less well-established in critical thinking in science learning, this is based on the results of observations on teaching relating to the phenomenon of momentum and impulse. Overcoming this, it is important to provide learning experiences for students to train their critical thinking skills. The current study aims to implement the discovery learning model on materials related to momentum and impulse phenomena, and evaluate its impact on students' critical thinking skills. Through experimentation (nonequivalent control group design) studies have been carried out by including a control group (traditional teaching) as a comparison. Students' critical thinking skills are measured using adequate instruments and have met the elements of validity. Study data were analyzed descriptively and statistically. The results of the study show that students' critical thinking skills have increased after learning using the discovery learning model. Based on the size of the pre-post test, students' critical thinking skills increased from quite critical to critical, the increase (gain) was in the moderate category. Unlike the case with traditional teaching, students' critical thinking skills remain with less critical criteria. The difference in the improvement of critical thinking between the two groups (discovery learning vs. traditional teaching) was statistically analyzed. The results of the analysis confirm the research hypothesis tested that there are significant differences in critical thinking skills between groups (discovery learning model vs. traditional teaching) in the material of momentum and impulse.